Gradient catalyst coating for a proton exchange membrane fuel cell operation under nonhumidified conditions - Lee, S.-Y.; Kim, H.-J.; Kim, K.-H.; Cho, E.; Oh, I.-H.; Lim, T.-H. (ELECTROCHEMICAL SOC INC, 2007)
Operation under nonhumidified conditions was demonstrated with a membrane electrode assembly (MEA) for a proton exchange membrane fuel cell. The Pt catalyst was coated with a gradient on the active area of a MEA; the catalyst amount was reduced gradually from cathode inlet to outlet. The MEA with the gradient coating method produced more water near the inlet site than that with the uniform coating method. The water was used to mitigate dryness of the MEA. The cell performance was improved by 17% at 800 mA/cm(2) under nonhumidified conditions by effective water management of the gradient coating method. (C) 2007 The Electrochemical Society.
Keywords: WATER MANAGEMENT; ELECTRODE; PEMFC; PERFORMANCE